Pengaruh Pembelajaran diluar Kelas (Outdoor Study) Terhadap Hasil Belajar IPA Siswa Kelas IV A SDN Paccinongan Unggulan - Ashar Ashar; Muliana Muliana; Roslynrosdiah Roslynrosdiah (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
This research aims to determine outdoor study on student learning outcomes in Natural Sciences subjects at SDN Paccinongan Unggulan. With the research problem "Is there an influence of outdoor study on the science learning outcomes of Class IV A students at SDN Paccinongan Unggulan?" The method used in this research is an experimental method in the form of pretest posttest control group design. The sample in this study was class IV A students of SDN Paccinongan Unggulan. Data collection techniques use direct observation, tests and documentation. The data analysis technique used in this research is a test/T-test data analysis technique where the collected data will be processed and analyzed using a normality test using SPSS version 22. The results of this research show that learning that applies outdoor learning has an effect on student learning outcomes in Natural Sciences (Science) subjects. In collecting data, research uses observation, documentation and test techniques. The results of this research show that there is an influence of outdoor study in learning natural sciences. This is proven in the t-test table (Independent Sample Test) with a significance value of 0.54 < 0.05, which means that H0 is rejected and Ha is accepted or tcount > ttable (26,610 > 2,056).